Additive Manufacturing of Parts from "Titanium Carbide- Titanium" Mechanically Activated Powder; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Pribytkov G. A. (2018, 2018)
Title screen